Continuous EEG in Pediatric Critical Care: Yield and Efficiency of Seizure Detection. Issue 5 (September 2017) - Sansevere, Arnold J.; Duncan, Elizabeth D.; Libenson, Mark H.; Loddenkemper, Tobias; Pearl, Phillip L.; Tasker, Robert C.
Abstract : Purpose: Our goal was to define the duration of continuous EEG (cEEG) monitoring needed to adequately capture electrographic seizures and EEG status epilepticus in the pediatric intensive care unit using clinical and background EEG features. Methods: Retrospective study of patients aged 1 month to 21 years admitted to a tertiary pediatric intensive care unit and undergoing cEEG (>3 hours). Clinical data collected included admission diagnosis, EEG background features, and time variables including time to first seizure after initiation of cEEG. Results: Four hundred fourteen patients aged 4.2 (0.75–11.3) years (median, interquartile range) were included. With a median duration of 21 (16–42.2) hours of cEEG monitoring, we identified electrographic seizure or EEG status epilepticus in 25% of subjects. We identified three features that could improve the efficiency of cEEG resources and provide a decision-making framework: (1) clinical history of acute encephalopathy is not predictive of detecting electrographic seizure or EEG status epilepticus, whereas a history of status epilepticus or seizures is; (2) normal EEG background or absence of epileptiform discharges in the initial 24 hours of recording informs the decision to discontinue cEEG; (3) failure to record electrographic ictal events within the first 4 to 6 hours of monitoring may be sufficient to predict the absence of subsequent ictal events. Conclusions: Individualized monitoring plans are necessary to increase seizure detection yield while improving resource utilization. A strategy using information from the clinical history, initial EEG background, and the first 4 to 6 hours of recording may be effective in determining the necessary duration of cEEG monitoring in the pediatric intensive care unit.